2021
DOI: 10.1101/2021.04.27.21256222
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Outcomes and Genomic characterization of SARS-CoV-2 isolated from Veterans in New England States

Abstract: BackgroundClinical and virologic characteristics of COVID-19 infections in veterans in New England have not been described.ObjectivesTo evaluate clinical and virologic factors impacting COVID-19 outcomes.Study DesignWe reviewed charts and sequenced virus from nasopharyngeal specimens with confirmed SARS-CoV-2 from 426 veterans in six New England states between April and September, 2020. Peak disease severity, hospitalization, and mortality were correlated to clinical, demographic, and virologic factors.Results… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Of 3950 Veterans in six New England states with confirmed SARS‐CoV‐2+ test before full vaccination during the study period, the average age was 60 ± 18 years, with 8% female and 81% White. An early cohort of 274 Veterans from our pilot study was included in this analysis to ensure the completeness of our analysis 10 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 3950 Veterans in six New England states with confirmed SARS‐CoV‐2+ test before full vaccination during the study period, the average age was 60 ± 18 years, with 8% female and 81% White. An early cohort of 274 Veterans from our pilot study was included in this analysis to ensure the completeness of our analysis 10 …”
Section: Resultsmentioning
confidence: 99%
“…US Veterans make a reasonably vulnerable population because of their average age of 58 years, which is higher than the average age of a US resident (38.5 years), and because Veterans are largely male (89%) 9 . At the beginning of the COVID‐19 era, we conducted a small pilot study on Veterans with COVID‐19 between April 2020 and September 2020 from the same region of New England and found age, dementia, and low BMI to be associated with mortality 10 . Here, we present the analysis of outcomes throughout the COVID‐19 era in these Veterans from the New England states.…”
Section: Introductionmentioning
confidence: 99%
“…An early cohort of 274 Veterans from our pilot study were included in this analysis to ensure the completeness of our analysis. 25 The most common comorbidities were chronic heart disease (31%), diabetes (27%), and chronic lung disease (23%). Of the 2,399 Veterans who became fully vaccinated in our study, 53% received the Pfizer vaccine, 41% received Moderna, and 6% received Janssen (Table 1b).…”
Section: Veteran Characteristicsmentioning
confidence: 99%
“…From the WGS data, we found that New England Veterans (>97%) were infected with B.1 and its sub-lineages with the D614G mutation in the early (n = 282) and middle period (n = 349) of the study. 25 In the late period (n = 277), the delta (B.1.617.2, 71%) lineages predominated (Supplemental Table 2). The most common and prominent lineages and subsequent hospitalizations within those lineages are shown in Figure 2.…”
Section: Viral Sequencingmentioning
confidence: 99%
See 1 more Smart Citation